A review of the role of paramedical staff in the healthcare sector and its impact on patient satisfaction and expectations: The Influence of Paramedical Staff on Patient Satisfaction in the Healthcare Sector (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Today's hospitals face a crisis because its patients aren't happy with the care they get.Understanding the wishes and desires of the patient is an important parameter that affects patientsatisfaction. Satisfied patients represent a very valuable asset, if they are satisfied, they will continue touse the service, and if they are not satisfied, they will tell twice as much to others about their badexperience. Paramedical professionals have become as the healthcare system's unsung heroes. Theseworkers are the primary points of contact between patients, family members, and the healthcareproviders they support. The purpose of this research is to analyze how the XXX hospital's paramedicalstaff affects patients' expectations and satisfaction. This is explanatory research which utilise linearregression and descriptive analysis. The population is all hospitalized patients with at least four days oftreatment in hospital. The results of the study confirmed that there is a significant impact of paramedicalstaff‟s role in patient satisfaction.